2010
DOI: 10.1149/1.3391820
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Kinetics of Mn[sub 1.5]Co[sub 1.5]O[sub 4]-Coated Haynes 230 and Crofer 22 APU for Solid Oxide Fuel Cell Interconnects

Abstract: The oxidation behavior of Mn1.5Co1.5normalO4 (MCO)-coated Haynes 230 (H230) and Crofer 22 APU was investigated between 700 and 900°C . The oxidation kinetics of the coated alloys was compared with that of base alloys at 800°C . An apparent two-stage kinetics behavior of the MCO-coated Crofer 22 APU was observed. The coating effectively reduced the oxidation rate constants of Crofer 22 APU by 5.5 times, whereas it did not seem to affect the oxidation kinetics of H230. The oxidation activation energies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 33 publications
2
18
1
Order By: Relevance
“…In both cases, the square of the weight gain per unit area (DW/A) 2 increases linearly with the increase in the isothermal oxidation time. This confirms that (DW/A) 2 as a function of oxidation time satisfies the parabolic kinetics law described by the following equation 24 :…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In both cases, the square of the weight gain per unit area (DW/A) 2 increases linearly with the increase in the isothermal oxidation time. This confirms that (DW/A) 2 as a function of oxidation time satisfies the parabolic kinetics law described by the following equation 24 :…”
Section: Resultssupporting
confidence: 79%
“…It also minimizes the interfacial contact area-specific resistance (ASR) between cathode and interconnect by limiting the growth of the Cr-based oxide scale, which has relatively low conductivity. 7 Efforts have been made by various groups [20][21][22][23][24][25][26][27][28] to demonstrate that a (Mn,Co) 3 O 4 spinel could be a promising barrier for interconnect applications in SOFCs. For example, Yang et al 25 found that Mn 1.5 Co 1.5 O 4 spinel coatings (prepared by a slurry screen-printing method) were effective in reducing the contact resistance and providing high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…These effects of the coating will be discussed in the following paragraphs. Parabolic rate constants from the present study may be compared to oxidation constants of spinel-coated steels from previous investigations [39,44,45]. The data are presented in Table 3.…”
Section: 2mentioning
confidence: 84%
“…In a recent study of Chen et al [39], the authors investigated the oxidation of a spinel coated and uncoated Crofer 22 APU at different temperatures. They found that the activation energy of coated and uncoated steel was similar and equal to w290 kJ mol À1 [39]. This value is comparable to the reported activation energy of Cr 3þ diffusion in Cr 2 O 3 (280 kJ mol À1 [34]).…”
Section: Steel Oxidation Mechanismmentioning
confidence: 99%
“…It was demonstrated that inter-granular oxidation and internal oxidation occurred at 982°C and 1093°C after 300 h exposure, respectively. Further, many researcher tried to improve the oxidation behavior of Haynes 230 by several methods, using alloying [22,23], electrical discharge alloying (EDA) [24,25], MOCVD [26] or various surface modification [27,28].…”
Section: Introductionmentioning
confidence: 99%